Back Cover: Effects of Aromatic Fluorine Substitution on Protonated Neurotransmitters: The Case of 2‐Phenylethylamine (Chem. Eur. J. 24/2016). Issue 24 (23rd May 2016) - Schütz, Markus; Bouchet, Aude; Chiavarino, Barbara; Crestoni, Maria Elisa; Fornarini, Simonetta; Dopfer, Otto
Abstract : Fluorination of pharmaceutical compounds is a common tool to modulate their physiochemical properties. The large effects of site‐specific aromatic fluorination of a protonated prototypical neurotransmitter (2‐phenylethylamine) have accurately been determined by infrared spectroscopy and dispersion‐corrected density functional theory calculations of ions isolated in the gas phase. The strengths of the various competing intramolecular noncovalent interactions (NH + ⋅⋅⋅π, NH + ⋅⋅⋅F) depend strongly on the fluorination site. Inset image of neurons courtesy of the National Institutes on Ageing/National Institutes of Health. More information can be found in the Full Paper by O. Dopfer et al. onpage 8124 ff.